A qualitative exploration of the barriers to and facilitators of clozapine monitoring in a secure psychiatric setting. (June 2021) - Blagden, Sarah; Beenstock, Jane; Auld, Natalie; Noblett, Steve; Limmer, Mark
Abstract : Aims and method: To explore the beliefs and understanding of staff and patients at a secure mental health unit regarding clozapine monitoring, and to identify barriers to and facilitators of monitoring. Qualitative semi-structured interviews and focus groups were conducted with 17 staff members and six patients. Results: Six key themes were identified. The key facilitator of effective monitoring was the motivation of staff to help patients to become independent and facilitate recovery. An important barrier was a lack of clarity around the roles of different staff groups in monitoring. Staff and patients widely supported the establishment of an in-patient clozapine clinic and perceived that it would prepare patients for discharge. Clinical implications: An in-patient clozapine clinic is a robust mechanism for clozapine monitoring in secure settings. The barriers and facilitators identified here could be applied to other secure units to guide their systems of clozapine monitoring.